Legal Certainty on PPAT Authority in Making Deed Outside of His Location - Prakoso, Bhim; Suarda, I Gede Widhiana; Wardana, Dendik Surya (Budapest International Research and Critics University, 2022)
This study aims to examine the legal certainty of the PPAT's authority in making deeds outside the area of his domicile. PPAT in carrying out its functions and authorities is limited by the working area, as regulated in PP PPAT in Article 12 paragraph (1) that the PPAT working area is